Cultural monuments in the Ferghana Valley (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article is about cultural monuments in the Fergana Valley. People have been living in the Fergana Valley since ancient times. The cultural monuments here cover the period from the Stone Age to the present day. the monuments belonging to the periods are found and studied.